SAT0158 Associates with and extent of reduced bone mineral density (bmd) in female rheumatoid arthritis (ra) patients: the oslo, truro, amsterdam (ostra) collaborative study. (1st June 2001) - Haugeberg, G; Lodder, M; Lems, W; Uhlig, T; Dijkmans, B; Kvien, T; Woolf, A
Abstract : Background: Objectives: To examine associates with and occurrence of reduced BMD in female RA patients from three European countries. Methods: 150 (50 from each country) consecutive female RA patients (ACR 1987 criteria, disease duration ≥5 yrs, age 50–70 yrs), visiting the out-patient rheumatology clinics were included. Study variables included clinical data, laboratory tests, hand X-ray (Larsen score) and BMD measurement. BMD (g/cm 2 ) was measured by dual energy X-ray absorptiometry (DXA) and adjusted for age, weight and height. A pooled European/US reference population, showing no substantial differences with published Norwegian, English, and Dutch reference populations, was used to calculate T-scores. Groups were compared by one way ANOVA and cross tabulation (Pearson Chi square test). To investigate associates for BMD reduction bi- and multi-variety statistical analyses were performed. Results: No significant differences between the countries were found for age, disease duration and rheumatoid factor, whereas weight and most disease related variables, including the use of prednisolone and treatment for osteoporosis, differed between the 3 groups. Percentage of patients having osteoporosis (T-score <-2.5 SD) at femoral neck was 21.3% in Oslo, 8.3% in Truro, and 18.4% in Amsterdam (P = 0.19) and at the spine 32.0%, 18.4% and 12.0% (P = 0.04), respectively. Mean (SD) BMD values are shown in the Table 1 . Using multivariate linear regression age, weight, total hand X-ray Larsen score, previous history of clinical fracture and ever use of DMARDs were independent associates for femoral neck BMD. For spine L2–4 weight, mean CRP last 12 months, ever use of DMARDs and current use of prednisolone were independent associates. Conclusion: Differences in femoral neck and spine BMD might reflect differences in life styles factors, disease activity and disease management between the countries.